The Influence of Price, Product Quality, and Halal Knowledge on Purchase Decisions for Fiesta Chicken Nugget Products with Purchase Intention as an Intervening Variable (Study on Consumers in Salatiga City) - Lisdiani, Nur Linna Isti; Annisa, Arna Asna (Invest Journal of Sharia & Economic Law, 2022)
Halal and non-halal meat zoning policies impact consumer intentions for a product. The product, Fiesta Chicken Nugget in Salatiga, is one of them. Whether positive or negative, the policy will impact the sale of processed meat products. This research is based on the background of processed chicken meat products, namely Fiesta Chicken Nugget in Salatiga, which is affected by the Halal Zoning policy. The study aimed to determine the effect of price, product quality, and consumer knowledge of halal on purchasing decisions for Fiesta Chicken Nugget products in Salatiga City, with buying interest as an intervening variable. This research uses quantitative research. The sampling technique used purposive sampling with a total of 100 respondents. This study conducted validity, reliability, correlation coefficient, determination coefficient, regression analysis, t-test with SPSS application and Sobel analysis to test the effect of intervening variables. The results of the hypothesis stated that price, product quality, halal knowledge, and buying interest had a positive and significant effect on purchasing decisions. While the study's results indicate that price and product quality affect buying interest, halal knowledge does not. Then the price, halal knowledge and buying interest do not affect purchasing decisions, but product quality does affect the Fiesta Chicken Nugget product.